Origin and Expansion of Ranvir Sena in Bihar - Chaudhary, S.N (2005)
Ranvir Sena emerged in central (now south) Bihar to counter challenges posed by the Nexalites. It emerged when the land-owners, most of whom were from the upper castes, found their individual efforts and state support unable to protect and promote their so-called legitimate economic rights and social and political domionance. A section of them got united and formed the sena. After its formation, the sena developed a structure, gathered resources and recruited young caste fellows as volunteers who were mainly from the middle and lower economic status. It committed massacres and forced the Naxalite movement to shift its operations from economic agenda to retaliation. Subsequently, neither of the two addressed the problems, of the common people. Currently, in certain areas there is a conflict between the Naxalites and the Ranvir Sena but in another area there is a compromise. But there is every doubt about the institutionalization of democratic values under the given scenario created by the verna-centric tradition, the Naxalite movement, the Ranvir Sena and the state. People’s issue relating to the people’s basic requirements still remains unattended.